2000
DOI: 10.1211/146080800128735917
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Activates Membrane-bound Guanylate Cyclase in PC12 Cells

Abstract: Resveratrol, found in wine and grapes, has cardioprotective and anticarcinogenic properties. The guanylate cyclase‐cyclic GMP (cGMP) system is known to mediate the effects of vasoactive hormone and ligands such as atrial natriuretic factor and nitric oxide. It is possible that resveratrol exerts its effects by activating guanylate cyclase. This study was conducted to examine whether resveratrol can affect the guanylate cyclase‐cGMP system in PC12 cells. The results showed that resveratrol dose‐dependently incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 28 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…Recently, we have shown that 17 -estradiol and resveratrol, a phytoestrogen, activate GC-A in PC12 cells (Chen et al 1998(Chen et al , 2000. Other antioxidants, such as dithiothreitol and vitamin C, also activate GC-A in PC12 cells (Chen et al 2001a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we have shown that 17 -estradiol and resveratrol, a phytoestrogen, activate GC-A in PC12 cells (Chen et al 1998(Chen et al , 2000. Other antioxidants, such as dithiothreitol and vitamin C, also activate GC-A in PC12 cells (Chen et al 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…The cell extracts were scraped and centrifuged for 15 min at 2000 g, and the supernatant fractions were extracted with water-saturated ether to remove trichloroacetic acid. The cGMP levels in the supernatants were determined by radioimmunoassay (Chang & Song 1993;Chen et al 1998Chen et al , 2000Chen et al , 2001a.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations